People or peoples; equality, autonomy and self-determination : the issues at stake of the International Decade of the World's Indigenous People (International Centre for Human Rights and DemocraticDevelopment MontrealCA, 1996)
Posits that the onus of achieving an international recognition of indigenous rights lies on indigenous peoples as well as government, and that the Aboriginal peoples of Canada can lead the way. Looks at the nature, scope and future prospects of the right of self-determination of peoples, notably as it relates to the leverage it can bring to ensure respect for the identity and fundamental rights of indigenous peoples.
DC